Intrathyroidal Thymic Tissue in an Adolescent with Graves’ Disease: Case Report and Review of Current Literature - Liane Eng; Lisa Underland; Leslie Lam (Case Reports in Pediatrics)
Intrathyroidal thymic tissue (ITT) is a benign entity found in children and young adolescents that often mimics a concerning thyroid nodule with microcalcifications on ultrasound. It is challenging for the clinician to distinguish between these two entities, which may lead to unnecessary invasive procedures. We report an adolescent female patient with Graves’ disease who underwent total thyroidectomy for a thyroid nodule concerning for malignancy for which the surgical pathology ultimately revealed ITT. As ITT is rarely found beyond childhood, the concurrent Graves’ disease may have led to persistence of thymic tissue in this patient. Several sonographic features can help in differentiating ITT from a concerning thyroid nodule. Once identified, ITT should be followed by serial imaging with anticipation of decreasing size or complete resolution over time.